Analisis Faktor Faktor Yang Berhubungan Dengan Kejadian Wasting Pada Bayi 6-24 Bulan - Utami, Febi Aidha; Fanaetu, Emnalia; Ndruru, Usniar; Sitio, Dormianti; Amarliana, Dea; Nababan, Tiarnida (Journal of Pharmaceutical and Sciences, 2025)
Background: Wasting, a form of acute malnutrition characterized by low weight-for-height, remains a critical public health problem in Indonesia. This condition increases the risk of child mortality and reflects short-term nutritional deficiencies. The prevalence of wasting in Indonesia continues to exceed the World Health Organization (WHO) threshold, underscoring the need for targeted interventions. Objective: This study aimed to analyze factors associated with wasting among children aged 6–24 months. Methods: A cross-sectional study was conducted at the UPT Puskesmas Bestari, Medan. The sample comprised 35 children aged 6–24 months selected using total sampling. Data were collected through interviews, nutritional status assessment (weight-for-height), and questionnaires. Data analysis included univariate analysis, bivariate analysis (Chi-square test), and multivariate analysis (logistic regression). Results: The prevalence of wasting was 71.4% (25 of 35 children). Bivariate analysis showed significant associations between wasting and inadequate dietary intake (p = 0.004), low maternal knowledge (p = 0.000), and low household income (p = 0.004). No significant associations were found between wasting and child sex (p = 0.421) or family size (p = 0.134). Multivariate analysis identified low maternal knowledge as the most dominant factor associated with wasting. Conclusion: Wasting among children aged 6–24 months is significantly influenced by inadequate dietary intake, low maternal knowledge, and low household income. Comprehensive interventions focusing on maternal nutrition education, strengthening household food security, and improving family economic capacity are essential to prevent wasting in this vulnerable age group.